Ответы и объяснения

2013-10-25T22:43:35+00:00
 \lim_{x \to \infty}  \frac{6x^2-5x+2}{4x^3+2x-1} = \lim_{x \to \infty}  \frac{x^3( \frac{6}{x} - \frac{5}{x^2} + \frac{2}{x^3}) }{x^3(4+ \frac{2}{x^2} - \frac{1}{x^3} )}
 \lim_{x \to \infty}  \frac{C}{x} =0:C=const
\lim_{x \to \infty} \frac{x^3( \frac{6}{x} - \frac{5}{x^2} + \frac{2}{x^3}) }{x^3(4+ \frac{2}{x^2} - \frac{1}{x^3} )} = \lim_{x \to \infty} \frac{x^3( 0 - 0 + 0) }{x^3(4+ 0 - 0 )}=0
На самом деле нули там нигде не стоят, но я их вписал для наглядности.